Scalp ulceration: a rare manifestation of giant cell arteritis. Issue 11 (2nd November 2019) - McDonald, Louise; Baker, Gavin; Kerr, Olga
Abstract : An 81-year-old woman presented with an enlarging, tender ulcer on her scalp over an 8-week period, attributing it to a prior graze with garden shears. C-reactive protein and erythrocyte sedimentation rate were elevated at 87.7 mg/L and 112 mm/hour, respectively. Incisional biopsies demonstrated ulceration and full thickness necrosis with no evidence of malignancy. Vasculitis was suggested as a likely cause of such extensive necrosis and subsequent temporal artery biopsy findings were consistent with giant cell arteritis. The patient was initially treated with high-dose oral prednisolone and achieved complete healing of the scalp necrosis within 12 months, with a gradual down-titration of steroid therapy thereafter. Scalp necrosis is a rare, potentially life-threatening complication of giant cell arteritis. This case highlights the importance of considering scalp necrosis as a manifestation of giant cell arteritis when assessing scalp ulceration. Prompt diagnosis and treatment can prevent significant morbidity and potential mortality.